On Kadison-Schwarz Type Quantum Quadratic Operators on 𝕄2ℂ. (17th April 2013) - Mukhamedov, Farrukh; Abduganiev, Abduaziz
Abstract : We study the description of Kadison-Schwarz type quantum quadratic operators (q.q.o.) acting from 𝕄 2 ℂ into 𝕄 2 ( ℂ ) ⊗ 𝕄 2 ( ℂ ) . Note that such kind of operators is a generalization of quantum convolution. By means of such a description we provide an example of q.q.o. which is not a Kadison-Schwartz operator. Moreover, we study dynamics of an associated nonlinear (i.e., quadratic) operators acting on the state space of 𝕄 2 ℂ .